NOTAS TAXONÔMICAS SOBRE Clathrodrillia aff. dautzenbergi (GASTROPODA, NEOGASTROPODA, DRILLIDAE) NO NORTE E NORDESTE DO BRASIL - Silva, Gutembergue Francisco da; Tenório, Deusinete de Oliveira (Revista Nordestina de Zoologia, 2014)
This paper presents taxonomic considerations on the occurrence of different morphotypes of Clathrodrillia dautzenbergi (Tippett, 1995) to the north coast and northeastern Brazil Specimens were collected in oceanographic expeditions by ship Almirante Saldanha, in the period 1967-1973. The study was conducted at the Laboratory of Malacology, Federal University of Pernambuco - UFPE. Clathrodrillia aff. dautzenbergi (Tippett, 1995) differs from Clathrodrillia dautzenbergi (Tippett, 1995) the general morphology of the shell and the total length. It is likely that this morphotype it is a new species for science.